Efektivitas Pelatihan BTCLS Berbasis Simulasi Bencana terhadap Respons Cepat Tim Medis: Scoping Review - Ririn Zuhairini; Anissa Rezki Alfatihah; M.Raihan Ramadhan; Risky Putri Maharani; Ni Putu Vika Purnamasari (CV. ITTC INDONESIA, 2025)
Basic Trauma and Cardiac Life Support (BTCLS) is an advanced emergency training program required by healthcare professionals to enhance rapid response capability, critical decision-making, and initial stabilization of disaster victims. In earthquake-prone areas, these competencies are essential due to the high risk of mass casualties and the limited time available for lifesaving interventions. This article aims to provide a comprehensive overview of the implementation of BTCLS training using disaster-based simulation as an effort to improve the rapid response of medical teams in earthquake-risk regions. This study applies the Arksey and O’Malley framework in conducting the analysis. The literature reviewed was obtained from PubMed, ScienceDirect, Scopus, CINAHL, and Taylor & Francis within the last five years. Identification and selection of articles followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) Moher 2009 guidelines. A total of 10 eligible articles were analyzed, consisting of 7 quantitative studies, 2 quasi-experimental studies, and 1 scoping review. This article summarizes key findings regarding the effectiveness of BTCLS disaster-based simulation, including improvements in knowledge, technical skills, teamwork, preparedness, and self-confidence among healthcare personnel. Disaster simulation has been shown to create a realistic and safe learning environment, enhancing coordination and communication abilities during earthquake emergency scenarios. Overall, BTCLS simulation-based training strengthens both individual and collective capacity of medical teams to respond quickly and efficiently during disaster situations.